ANALISIS DIMENSI GOTONG ROYONG PADA CERITA ANAK “Odi’ Neng Polo Buja” Karya M Ridwan - Framz Hardiansyah; Kholifatus Saadah; Putri; Mutiara Sukma Arofah; Nabila Sya’bani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to find out the dimensions of mutual cooperation contained inchildren's stories entitled Odi' Neng Polo Buja which is a story by Ridwan consistingof two languages, namely Madurese and Indonesian, as one of the media to be usedin learning. The method used in this study is qualitative with content analysismethods and data collection techniques in the form of literature studies,documentation and data analysis. Based on the results of the research that hasbeen carried out, it was found that in the children's story entitled Odi' Neng PoloBuja, there are several dimensions of mutual cooperation, namely the elements ofcollaboration, sharing, and care. In the story of Odi' Neng Polo Buja, there isbehavior that reflects the attitude of mutual cooperation. The dimension of mutualcooperation in the child's story can be seen from the attitude ofcollaboration/cooperation carried out by Iping, Inung and his friend when helpingtheir father Iping harvest salt in the pond.